KELAS LITERAT TERHADAP PERKEMBANGAN LITERASI ANAK TUNARUNGU DI TKLB KARYA MULIA SURABAYA - Ary Pratiwi, Gadis (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   Hearing impairment made the children’s speaking development late. The disturbance of the children’s speaking development caused complex development problem. As the low information received by the children it had impact to their literacy development. Therefore, developing literacy should be given as early as possible. Looking at the importance of speaking ability in daily life the skill should be developed. One of them was by applying literate class. This research had purpose to analyze the influence of literate class toward literacy development of hearing impairment children in Special Kindergarten (TKLB) Karya Mulia Surabaya. This research used quantitative approach with pre experiment kind and the research arrangement was “one group pre-test – post-test design”. The subject was hearing impairment children of Kindergarted class in TKLB Karya Mulia Surabaya numbering 7 children. The data collection technique used test and observation. The data analysis technique used statistic non parametric with “Wilcoxon Match Pairs Test”. The result of data, analysis indicated that the usage of literate class influenced significantly toward literacy development of hearing impairment children in TKLB Karya Mulia Surabaya.   Keywords : Literate Class, Literacy Development